2021
DOI: 10.1177/1687814020987329
|View full text |Cite
|
Sign up to set email alerts
|

Detection and localization of multiple small damages in beam

Abstract: Localizing small damages often requires sensors be mounted in the proximity of damage to obtain high Signal-to-Noise Ratio in system frequency response to input excitation. The proximity requirement limits the applicability of existing schemes for low-severity damage detection as an estimate of damage location may not be known  a priori. In this work it is shown that spatial locality is not a fundamental impediment; multiple small damages can still be detected with high accuracy provided that the frequency ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…It should be noted that the range fWR incorporates only the first four natural frequencies and there is no need to acquire the data of higher natural frequencies for accurate detection. 6…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the range fWR incorporates only the first four natural frequencies and there is no need to acquire the data of higher natural frequencies for accurate detection. 6…”
Section: Resultsmentioning
confidence: 99%
“…It implies that when the cepstrum technique is employed along with the baseline-free FRF curvature method, it enhances the effectiveness of the method against noise. The range of fWR: It has been established that for detection and localization of less severe single/multiple damages by using the baseline-free FRF curvature method, the range fWR must include higher frequencies. 6 By investigation, it was found that the results were significantly improved by readjusting the range of fWR from fifth to tenth natural frequencies. However, it is a challenging task to obtain accurate data at higher natural frequencies in an actual experimental setup.…”
Section: Effect Of Measurement Noisementioning
confidence: 99%
See 1 more Smart Citation
“…The first damage scenario, denoted by DS1, corresponds to a single damaged area of 40 mm × 40 mm at the center of the plate, whereas the second, designated DS2, has two damaged areas of 40 mm × 40 mm each: one at the center an another at the upper right corner. The multiple damage scenario DS2 is considered here, since it is still a challenge to localize multiple damage, in particular if it is small, because in such a case the noise influence is most important and may lead to false positives (Nayyar et al. , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Some other important results in the field can be found in the literature. [25][26][27][28][29][30][31] Many investigations have been done in the term of Timoshenko beam with different cross-sections and boundary conditions; nevertheless, none considered the shapes of Koch snowflake iterations as the beam's cross-section. We, for the first time, in an original and novel study, analyzed the Timoshenko beam with the first, second, and third iteration of the Koch snowflake cross-section, which are unique structures.…”
Section: Introductionmentioning
confidence: 99%